A Multicultural Education Model for Understanding Child Legitimacy: Harmonization of Family Law and Bugis Customary Law - Sulaeman, Sulaeman; Nuhung, Sarman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The issue raised is the disharmony between National Family Law and Bugis Customary Law regarding the legitimacy of illegitimate children, which often has implications for children's rights and inheritance. The purpose of this study is to formulate a multicultural education model based on local Bugis values ​​(siri' and pacce) to promote a harmonious understanding of child legitimacy in indigenous communities. This study uses qualitative methods with a socio-legal approach and case studies in South Sulawesi. Data were collected through in-depth interviews with traditional leaders, legal experts, and education practitioners, as well as analysis of legal documents and customary texts. The results indicate that an effective multicultural education model must integrate local wisdom into the curriculum to bridge differences in norms, focusing on the role of the family and customary institutions as primary mediators. The main contribution of this study is to present a theoretical and practical framework that can be applied to minimize legal conflicts and ensure comprehensive protection of children's rights, while strengthening Bugis cultural identity within the context of national law.